Nanostructured TiO2 synthesized by different methods: Relationship between TiO2 porosity and crystalline-amorphous structure - F. El Koulali; M. Ouzzine; L. Cano-Casanova; M.C. Román-Martínez; M.A. Lillo-Ródenas (Chemistry of Inorganic Materials, 2024)
The present manuscript focuses on important aspects regarding TiO2, which is typically used in many applications. On one hand, a thorough review of methods for synthesizing nanostructured TiO2 is presented. Using these methods, and different post-synthesis heat-treatment conditions, close to thirty TiO2 materials have been prepared, and their porous texture and crystalline and amorphous structure have been characterized. In this large number of samples, the porous texture characterization has revealed a high contribution of mesoporosity in a large number of the synthesized materials, being in many materials around 60–70 %. Moreover, different percentages of crystalline phases, anatase, brookite, rutile, and amorphous titania are developed depending on the TiO2 preparation conditions. These fractions have been determined from X-ray diffraction data using the “simple” characterization method reported by Cano-Casanova et al., inspired by Jensen et al., and Bellardita et al., also exploring its limitations. This analysis has allowed assessing a linear relationship between porosity, particularly between the surface area, and the amorphous phase content in titanium dioxide. A relationship had been previously suggested in the literature, but never correlated in such a way. In summary, the present study constitutes a tool to help other researchers select the most suitable method for synthesizing nanostructured TiO2 materials with target properties and, also, to characterize them, and have a very easy and straightforward estimation of TiO2 amorphous phase content after the determination of their surface areas.